Four Different Methods to Hybrid Simulated Kalman Filter (SKF) with Gravitational Search Algorithm (GSA) - Badaruddin, Muhammad; Zuwairie, Ibrahim; Kamil Zakwan, Mohd Azmi; Khairul Hamimah, Abas; Nor Azlina, Ab. Aziz; Nor Hidayati, Abd Aziz; Mohd Saberi, Mohamad (Universiti Malaysia Pahang, 2016)
This paper presents a performance evaluation of a new hybrid Simulated Kalman Filter and Gravitational Algorithm (SKF-GSA), for continuous numerical optimization problems. Simulated Kalman filter (SKF) was inspired by the estimation capability of Kalman filter. Every agent in SKF is regarded as a Kalman filter. Inspired by the Newtonian gravitational law,gravitational search algorithm (GSA) has been introduced in 2009. Four methods (models) to hybridize SKF and GSA are proposed in this paper. The performance of the hybrid SKF-GSA algorithms is compared against the original SKF using CEC2014 benchmark dataset for continuous numerical optimization problems. Based on the analysis of experimental results, we found that model 3 and model 4 are performed better than the original SKF.